The Effect of Gluteus Medius Muscle Activation on Lower Limb Three-dimensional Kinematics And Kinetics in Male and Female Athletes during Three Drop Jump Heights - Nowak, Stephanie Christine (Université d'Ottawa / University of Ottawa, 2012)
Women are four to eight times more likely to injure their anterior cruciate ligament (ACL) compared to men. It is most commonly injured through a non-contact mechanism during game time situations. During landings, women display valgus collapse, where a less active gluteus medius muscle (GMed) may be unable to control the internal rotation of the thigh, causing an increase in knee joint abduction angle, augmenting the risk of ACL injury. This study’s purpose was to determine the difference between 12 male and 12 female athletes in muscle activity, specifically the GMed, and the 3D kinematics and kinetics of the lower-limb during drop jump landings from three heights; maximum vertical jump height, tibial length, and a commonly used height of 40cm. Results showed that females had greater hip adduction and knee abduction angles compared to men. The GMed activity showed no significant differences between sexes at each drop jump height.
Keywords: gluteus medius; ACL injury; intramuscular electrodes; drop jumps; sex differences